Path-dependent selection—a bridge between natural selection and neutral selection - Wang, Rui-Wu; Yu, Yun-Yun; Shi, An-Na; Zhu, Qi-Kai; Li, Minlan; Wang, Chao; Tao, Yi; Han, Jia-Xu (Frontiers in Ecology and Evolution, 2023)
Path-dependent selection follows the premise of complete symmetry in the neutral theory of selectionmutations in the natural world are entirely based on statistical randomness, lacking directionality, and thus do not exhibit differences in fitness. In specific spatiotemporal conditions, however, positive feedback effects in the environment cause the symmetry in neutral selection to break down, resulting in the emergence of recursive effects -Lamarckian active selection or inheritance of acquired characteristics. Active selection by organisms' contrasts with passive selection under natural selection pressure of the environment under the influence of positive feedback in suitable environments, creating a mutual antagonistic effect in multidimensional spatial conditions and thus forming paths. Path-dependent selection proposes that the evolutionary process of organisms is a selection process based on path frequencies rather than an increase in fitness, with a strong reliance on the paths it has taken in the past. Because of the existence of transition probabilities between different paths (such as plasmid transfer, transposons, and ecological interactions in biological evolution), path formation will exhibit acceleration or deceleration effects, explaining Gould's principles such as punctuated equilibrium. When environmental selection pressure is low or zero, most or all paths (like neutral selection outcomes) may be possible. The frequencies of different paths will differentiate as environmental selection increases, with paths with higher frequencies being more easily selected. When the evolutionary process or history has no impact on the evolution of the paths themselves (a static, equilibrium state), the path with the highest frequency is the shortest or optimal path used by evolutiona result consistent with Darwin's theory of natural selection. Path-dependent selection, which draws inspiration from modern physics, particularly path integral methods in quantum mechanics, may provide us with a new perspective and approach to explaining the evolution of life.